Improving Critical Thinking Skills through Problem-Based Learning Models with Argumentation in the Group Theory Course - Setyawati, Rina Dwi; Budi Waluya; isnarto; Putriaji Hendikawati (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
Argumentation is one of the factors considered in measuring critical thinking skills. This study aims to evaluate the effectiveness of the Argumentationbased Problem-Based Learning model in enhancing the critical thinking skills of prospective mathematics teachers. This study used a post-test only control design involving 53 prospective mathematics teacher students at UPGRIS, consisting of two classes, namely the experimental class and the control class with a purposive sampling technique. The data collection technique was carried out through a critical thinking ability test. The data analysis technique used was a prerequisite test analyzing with a paired sample t-test hypothesis test, independent sample t-test and N-gain. The results showed that the experimental class experienced an increase in critical thinking skills in the group theory course. The critical thinking skills of the experimental class with the Problem Based Learning and Argumentation model learning were better than the control class with a sig <0.05. The increase in students' critical thinking skills increased significantly with a moderate category (N-gain = 0.47). The indicator of critical thinking skills in the criteria stating that there are problems in the information provided experienced the greatest increase, while the indicator of constructing valid arguments experienced the lowest increase. There was an increase in the ability of prospective teachers in constructing arguments but in the low criteria. The ability to construct arguments needs to be given special attention in efforts to improve critical thinking skills.